Disputes and their Resolution in the Electronic Communications Market - Gjika, Jonida (European Journal of Multidisciplinary Studies, 2016)
This short treatment introduces the concept of potential disputes in the electronic communications market, their typology and the background in which exist premises to arise desputes in this market. Broadly represents the forecast of domestic regulatory and legal framework for the treatment of desputes existing in this market, approximation of legislation with EU directives, ways to resolve disputes arising in the potential levels of the market in which those disputes arise. As a summary is treated the concept of internal market/markets structure as domestic part of the electronic communications market, identifying the importance of "treatment" of state and regulatory policies, and their impact on the design, planning and management strategies of the market players. The case of Albania is breafly treated regarding to the aspects referred in topic, closely linked with desputes and their treatment, paying a special importance administrative settlement in procedural terms. Identification of regulatory effect, as potential to be measured and compared with analog markets, and services offered in these markets with other countries, regional, of EU, or wider and mainly in the aspect from they derive, which highly propable are connected to services offered - their tariff - quality products / services. Briefly on the importance of effective competition and its impact on the number of disputes arising in such a market, considering liberalization as factor of market as fundamental aspect in the development of the market, increasing the number of providers of products / services and legal remedies forecast with specific criteria that maximize protection of users of products / services offered.
Keywords: Market, electronic communications, disputes, service providers, users, products/services, regulator, administrative solutions.